OVERCOMING STUTTERING THROUGH MULTIMODAL CORRECTION PROGRAMS - Abdullayeva Karomat Islom qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the effectiveness of multimodal correction programs in treating stuttering in children. Multimodal approaches integrate speech therapy, psychological interventions, sensory–motor training, and technological tools to address the complex nature of stuttering. The research highlights how combining behavioral, cognitive, rhythmic, respiratory, and articulatory-based techniques provides a more holistic and sustainable improvement in speech fluency. The article also discusses the role of family involvement, individualized therapy plans, and interactive learning environments in optimizing therapeutic outcomes.